The Influence of the Quality of Islamic Guidance and Counseling Services and Peer Environment on Self-Awareness in Overcoming Academic Procrastination (Research at SMAN 1 Dayeuhkolot) - Atqiya, Syifaul; Kusnawan, Aep; Mujib, Abdul (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to examine the influence of the quality of Islamic guidance and counseling services and peer groups on self-awareness in overcoming academic procrastination. This issue is relevant considering that academic procrastination remains a challenge among students, characterized by a tendency to postpone assignments and prioritize less relevant activities. This study used a quantitative approach with multiple linear regression analysis techniques. The population and sample were 36 students of SMAN 1 Dayeuhkolot identified as having academic procrastination behavior.The results of the study indicate that the quality of Islamic guidance and counseling services (X1) and peer support (X2) partially and simultaneously have a significant influence on self-awareness in overcoming academic procrastination (Y). The significance values found for both variables (0.00 and 0.000) are less than 0.05, which confirms that the research hypothesis is accepted. The magnitude of the influence of these two independent variables on the dependent variable is 76.3%. This means that 76.3% of the increase in students' self-awareness can be explained by the quality of Islamic guidance and counseling services and support from the peer support environment. The remainder (23.7%) is influenced by other factors outside the study.The conclusion of this study is that strengthening the quality of Islamic guidance and counseling services and creating a positive peer environment are effective strategies for increasing students' self-awareness and, ultimately, overcoming academic procrastination.